2004
DOI: 10.1002/jcp.20172
|View full text |Cite
|
Sign up to set email alerts
|

The acrosomal vesicle of mouse sperm is a calcium store

Abstract: Subsequent to binding to the zona pellucida, mammalian sperm undergo a regulated sequence of events that ultimately lead to acrosomal exocytosis. Like most regulated exocytotic processes, a rise in intracellular calcium is sufficient to trigger this event although the precise mechanism of how this is achieved is still unclear. Numerous studies on mouse sperm have indicated that a voltage-operated Ca2+ channel plays some immediate role following sperm binding to the zona pellucida glycoprotein ZP3. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 67 publications
2
108
0
1
Order By: Relevance
“…The acrosome behaves as an internal store of releasable calcium (41)(42)(43)(44); efflux from this reservoir through inositol 1,4,5 triphosphate (IP 3 )-sensitive channels is required for the AR initiated by all inducers (32,33,41,45). We had previously demonstrated that Rab3A acts in the AR before the release of calcium from the intracellular store (32).…”
Section: Resultsmentioning
confidence: 99%
“…The acrosome behaves as an internal store of releasable calcium (41)(42)(43)(44); efflux from this reservoir through inositol 1,4,5 triphosphate (IP 3 )-sensitive channels is required for the AR initiated by all inducers (32,33,41,45). We had previously demonstrated that Rab3A acts in the AR before the release of calcium from the intracellular store (32).…”
Section: Resultsmentioning
confidence: 99%
“…The acrosome behaves as an internal store of releasable calcium (19,47,53,54); efflux from this reservoir through IP 3 -sensitive channels is required for the AR initiated by all inducers (22,28,33,55). Results presented in Figs.…”
Section: Arf6 Promotes Calcium-regulated Exocytosismentioning
confidence: 93%
“…The second sustained increase in cytosolic Ca 2þ is controlled by inositol 1,4,5-trisphosphate receptor (IP 3 R) channels localized in the outer membrane of the acrosomal vesicle (Walensky and Snyder, 1995). The latter acts as an intracellular Ca 2þ store (De Blas et al, 2002;Herrick et al, 2005), the emptying of which activates storeoperated Ca 2þ channels, potentially composed of members of the transient receptor potential (TRP) family of cation channels (Jungnickel et al, 2001;Darszon et al, 2005). Remarkably, mimicking the influx of Ca 2þ mediated by store-operated Ca 2þ channels by incubating permeabilized spermatozoa in high external Ca 2þ , led to the intriguing observation that the sustained increase of intracellular Ca 2þ resulting from Ca 2þ…”
mentioning
confidence: 99%